Simulative governance: on the collaborative narrative of civil society participation in the CDM stakeholder framework. Issue 3 (3rd May 2016) - Kuchler, Magdalena; Lövbrand, Eva
ABSTRACT: The Kyoto Protocol's Clean Development Mechanism (CDM) is often cited as an exemplar of new, hybrid forms of global environmental governance operating at the public–private interface. Practically, enacting this arrangement involves a wide range of non-state actors. This broad involvement is here assumed to mark a shift towards more polycentric and networked modes of governance in which agents collaborate as 'stakeholders' in the process of consensual rule-setting and implementation. Using post-political critique, the depoliticising effects of the stakeholder framework on civil society actors are interrogated, using formal and informal participation opportunities to raise concerns regarding specific CDM projects. The analysis suggests that the CDM's collaborative narrative of stakeholding structurally fails to stimulate public (re)engagement and is, instead, a prime example of simulative governance that struggles to achieve the simultaneity of two incompatibilities: the participatory revolution and the post-political turn.